1988
DOI: 10.1080/02772248809357310
|View full text |Cite
|
Sign up to set email alerts
|

The human serum paraoxonase—Polymorphism and specificity

Abstract: Human serum contains EDTA-sensitive (Ca ++ -dependent) and EDTA-stable (albumin) paraoxonases which hydrolyse paraoxon, 0,0-diethyl,0-4-nitrophenyl phosphate.In Caucasians the EDTA-sensitive enzyme shows a genetically determined polymorphism which is governed by two alleles. In typical Mongoloid or Negro populations this polymorphism is expressed to a lesser degree, and in a few samples (e.g. Aborigines) it cannot be observed at all. The distribution of the activity of the EDTAstable (albumin) paraoxonase is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 120 publications
0
37
2
3
Order By: Relevance
“…Evaluation of the Amount of Bound Detergent-HuPON1 was loaded on a 6-ml Q-Sepharose gel (see "Detergent Exchange") equilibrated in 0.36 mM C 12 E 8 in buffer A, washed by 60 ml of buffer A* (0.36 mM radiolabeled 14 C 12 E 8 at 0.031 Ci/ml in buffer A), and eluted by buffer B* (0.36 mM 14 C 12 E 8 at 0.031 Ci/ml in buffer A with NaCl 280 mM). 200 l of the more concentrated fraction (0.3 mg/ml) was loaded on a gel filtration column (Superose 12 HR 10 -30 from Amersham Biosciences) previously equilibrated in B* and eluted in the same buffer.…”
Section: Evaluation Of the Amount Of Detergent Released Upon Protein mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the Amount of Bound Detergent-HuPON1 was loaded on a 6-ml Q-Sepharose gel (see "Detergent Exchange") equilibrated in 0.36 mM C 12 E 8 in buffer A, washed by 60 ml of buffer A* (0.36 mM radiolabeled 14 C 12 E 8 at 0.031 Ci/ml in buffer A), and eluted by buffer B* (0.36 mM 14 C 12 E 8 at 0.031 Ci/ml in buffer A with NaCl 280 mM). 200 l of the more concentrated fraction (0.3 mg/ml) was loaded on a gel filtration column (Superose 12 HR 10 -30 from Amersham Biosciences) previously equilibrated in B* and eluted in the same buffer.…”
Section: Evaluation Of the Amount Of Detergent Released Upon Protein mentioning
confidence: 99%
“…Fig. 7 shows the elution profiles of 200 and 100 l of HuPON1 injected at 0.3 and 1.2 mg/ml, respectively, in the presence of 0.36 mM radioactive 14 C 12 E 8 and the measurement of the radioactivity on the recovered fractions. From the measurement on three fractions on each of the two gel filtration columns eluted with radiolabeled C 12 E 8 , bound detergent ⌬ det was estimated to be 0.9 and 1.1 g of C 12 E 8 per g of HuPON1.…”
Section: Table II Equilibrium Sedimentation Of Hupon1 In the Presencementioning
confidence: 99%
“…Maternal urinary dialkyl phosphate metabolite levels in an agricultural population are correlated with shortened gestational length, a higher number of abnormal reflexes in neonates, and poorer neurodevelopment in young children (Eskenazi et al, 2004(Eskenazi et al, , 2007Young et al, 2005). Paraoxonase 1 (PON1) is an OP-hydrolyzing enzyme with high activity for detoxifying chlorpyrifos oxon (CPO) among many OPs (Geldmacher-von Mallinckrodt and Diepgen, 1988;Furlong et al, 1988). PON1 levels in children are often lowest at birth and can take up to 24 months or longer to reach adult levels (Augustinsson and Barr, 1963;Cole et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that individuals with low serum activity of this enzyme would be expected to have low ability to metabolize organophosphate compounds ( Geldmacher-von Mallinckrodt and Diepgen, 1988). Earlier studies on animals have also demonstrated the role of PON1 in decreasing the toxicity of organophosphate pesticides.…”
Section: Results:-mentioning
confidence: 99%